Delay discounting of the μ-opioid receptor agonist remifentanil in rhesus monkeys. Issue 2 (April 2016) - Maguire, David R.; Gerak, Lisa R.; France, Charles P.
Abstract : Although increased impulsivity (delay discounting) is an important risk factor for drug abuse, the impact of delay on drug taking has received relatively little attention. This study examined delay discounting of the μ-opioid receptor agonist remifentanil in rhesus monkeys ( n =4) responding for intravenous infusions under a concurrent choice procedure. Dose–effect curves for remifentanil were determined by varying the dose available on one lever (0.001–0.32 μg/kg/infusion) while keeping the dose available on the other lever (0.1 μg/kg/infusion) the same. Dose–effect curves were determined when both infusions were delivered immediately and when delivery of the fixed dose was delayed (15–180 s). When both doses of remifentanil were delivered immediately, monkeys chose the large dose. Delaying delivery of the fixed dose reduced choice of that dose and increased choice of small immediately available doses. Extending previous studies, these results show that the effects of delay on choice between two doses of a μ-opioid receptor agonist are consistent with hyperbolic discounting. Delaying delivery of a preferred reinforcer (e.g. large dose of drug) reduces its effectiveness and increases the effectiveness of small immediately available doses. This effect of delay, particularly on drug self-administration, might contribute to drug abuse.